Building Operating and Delivery Service - Apriz; Limakrisna, Nandan (Green Publisher, 2024)
To obtain high debtor loyalty, companies must create a product that can provide more value for consumers. Therefore, the study of consumer value is important. Loyal or not loyal customers depend on the company's ability to provide value services (service value) by the perceived value of their customers, because now customers are confronted with a wide choice of bank services, and customers will choose the product and services that provide more value. The object of research into a variable in this research is the performance of service operations strategy that includes physical facilities, equipment, information and technology, human resources, the research method used is the method descriptive survey and explanatory survey method.